Cytotoxic cardenolides from the latex of Calotropis procera. Issue 20 (15th October 2015) - Mohamed, Nadia H.; Liu, Miaomiao; Abdel-Mageed, Wael M.; Alwahibi, Lamya H.; Dai, Huanqin; Ismail, Mady Ahmed; Badr, Gamal; Quinn, Ronald J.; Liu, Xueting; Zhang, Lixin; Shoreit, Ahmed A.M.
Graphical abstract